The Effect of Compensation and Work Environment on Work Ethic Which Impact on Employee Performance at PT. Mitraindo Perkasa in Jakarta - Anggada Bayu Seta (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
This study aims to determine the effect of compensation and work environment on work ethic, which impacts employee performance at PT. Mitraindo Perkasa in Jakarta. The method used is explanatory research with a sample of 125 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study Compensation has a significant effect on work ethic by 26.7%; hypothesis testing obtained a significance of 0.000 <0.05. The work environment significantly affects work ethic by 41.5%; hypothesis testing acquired a value of 0.000 <0.05. Finally, compensation and work environment simultaneously considerably affect the work ethic of 47.2%; hypothesis testing obtained a significance of 0.000 <0.05.